Chapter Servitù ed emancipazione - Panero, Francesco (Firenze University Press, 2025)
The author highlights the characteristics of servitude and personal emancipation in the last centuries of the Middle Ages, tracing them not only to their legal dimension but to the decisive influence of economic and social changes that often escaped the control of the lords, for example with the settling of serfs and with the recognition of the possession of lands under concession for an indefinite period and the right to cede them which offered them the possibility of mixing with the free peasants. Personal manumissions having disappeared in the 12th century, collective manumissions which were still widespread in the following century show precisely how some of them, for example the one promoted by the municipality of Vercelli in 1243, ended up being limited to mere fiscal emancipation because the interested parties were already free men.